2018
DOI: 10.1007/s10995-018-2476-3
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Survival in Nigeria: A Pre-post Evaluation of an Integrated Maternal and Neonatal Health Program

Abstract: Introduction Nigeria contributes more obstetric, postpartum and neonatal deaths and stillbirths globally than any other country. The Clinton Health Access Initiative in partnership with the Nigerian Federal Ministry of Health and the state Governments of Kano, Katsina, and Kaduna implemented an integrated Maternal and Neonatal Health program from July 2014. Up to 90% women deliver at home in Northern Nigeria, where maternal mortality ratio and neonatal mortality rates (MMR and NMR) are high and severe challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…27 Despite these global recommendations and endorsements and despite pilot implementation and scale up projects conducted in India Nigeria, Ethiopia, Niger, Timor Leste and Colombia, there have been fewer publications on how the NASG is accepted and used by clinicians and health systems. [28][29][30][31][32][33][34][35] The reports on NASG use in Purina and Gaya district from Bihar revealed that the interviews and discussion with stakeholders reflected that even after training and appropriate introduction of the practice of using the NASG, the initiative did not translate into making a difference in ameliorating the situation of PPH management in the health facilities over a period of the following 6 months. The NASG were procured by national health mission and supplied in ambulances to the facilities.…”
Section: Discussionmentioning
confidence: 99%
“…27 Despite these global recommendations and endorsements and despite pilot implementation and scale up projects conducted in India Nigeria, Ethiopia, Niger, Timor Leste and Colombia, there have been fewer publications on how the NASG is accepted and used by clinicians and health systems. [28][29][30][31][32][33][34][35] The reports on NASG use in Purina and Gaya district from Bihar revealed that the interviews and discussion with stakeholders reflected that even after training and appropriate introduction of the practice of using the NASG, the initiative did not translate into making a difference in ameliorating the situation of PPH management in the health facilities over a period of the following 6 months. The NASG were procured by national health mission and supplied in ambulances to the facilities.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] Neonatal deaths and stillbirths have declined at a slower rate than other under-5 deaths. [6,7,8] Therefore, more concentration is needed on the neonatal population, which is part of Sustainable Development Goals (SDG), specifically (SDG 3.2).Birth asphyxia, perinatal asphyxia, and neonatal asphyxia are all terms referring to the same neonatal complication of a hypoxic event before, during or shortly after birth. [4,9,10,11] Birth asphyxia is not just a medical diagnosis, but also a nursing and midwifery concern, as the standard neonatal care after birth is prompt drying, stimulation and warmth, which is sufficient intervention to initiate and maintain breathing for 99% of neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to include CHWs and traditional birth attendants into NOC provide important examples of both features. 66,67 Extending the reach of NOC is especially important when the network aims to provide services to hard-toreach and underserved groups, such as people in rural areas, those living in extreme poverty, or experiencing other circumstances that increase their vulnerability to poor health outcomes. Vulnerable groups are likely to have less agency to navigate poorly integrated nodes of a nominal network, so methods that diversify locations of care, bring care closer to where they reside, or otherwise emphasize and facilitate continuity of care, can save lives.…”
Section: Flexibility and Extending Reachmentioning
confidence: 99%